Multiple Description Coding with Side Information: Practical Scheme and Iterative Decoding - Béatrice Pesquet-Popescu; Christine Guillemot; Olivier Crave (EURASIP Journal on Advances in Signal Processing, 2009)
Multiple description coding (MDC) with side information (SI) at the receiver is particularly relevant for robust transmission in sensor networks where correlated data is being transmitted to a common receiver, as well as for robust video compression. The rate-distortion region for this problem has been established in (Vaishampayan 1993). Here, we focus on the design of a practical MDC scheme with SI at the receiver. It builds upon both MDC principles and Slepian-Wolf (SW) coding principles. The input source is first quantized with a multiple description scalar quantizer (MDSQ) which introduces redundancy or correlation in the transmitted streams in order to take advantage of the path diversity. The resulting sequences of indexes are SW encoded, that is, separately encoded and jointly decoded. While the first step (MDSQ) plays the role of a channel code the second one (SW coding) plays the role of a source code, compressing the sequences of quantized indexes. In a second step, the cross-decoding of the two descriptions is proposed. This allows us to account for both the correlation with the SI as well as the correlation between the two descriptions.